2019
DOI: 10.1080/22221751.2019.1677446
|View full text |Cite
|
Sign up to set email alerts
|

GILT restricts the cellular entry mediated by the envelope glycoproteins of SARS-CoV, Ebola virus and Lassa fever virus

Abstract: Interferons (IFNs) control viral infections by inducing expression of IFN-stimulated genes (ISGs) that restrict distinct steps of viral replication. We report herein that gamma-interferon-inducible lysosomal thiol reductase (GILT), a lysosome-associated ISG, restricts the infectious entry of selected enveloped RNA viruses. Specifically, we demonstrated that GILT was constitutively expressed in lung epithelial cells and fibroblasts and its expression could be further induced by type II interferon. While overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…4D). In agreement with our previous report, expression of GILT inhibited SARS-CoVpp infection (38). To further confirm the role of LY6E in HCoV-OC43 infection, we showed that ectopic expression of LY6E in C3A and A549 cells significantly reduced their susceptibility to the virus infection, whereas reducing the expression of LY6E in HepG2 cells by shRNA knockdown significantly increased HCoV-OC43 infection (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4D). In agreement with our previous report, expression of GILT inhibited SARS-CoVpp infection (38). To further confirm the role of LY6E in HCoV-OC43 infection, we showed that ectopic expression of LY6E in C3A and A549 cells significantly reduced their susceptibility to the virus infection, whereas reducing the expression of LY6E in HepG2 cells by shRNA knockdown significantly increased HCoV-OC43 infection (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, while IFITM proteins inhibit the entry of all the other human CoVs, HCoV-OC43 hijacks human IFITM2 or IFITM3 as entry factors to facilitate its infection of host cells (42, 43). We also demonstrated recently that GILT suppresses the entry of SARS-CoV, but not other human CoVs (38). As reported herein, in our efforts to identify host factor(s) determining the differential susceptibility of two closed related human hepatoma cell lines to HCoV-OC43 infection, we found that LY6E potently suppresses the infectious entry of all the human CoVs, including the currently pandemic SARS-COV-2.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interferons (IFNs) are the primary antiviral cytokines that mediate innate and adaptive immune control of virus infection by inducing hundreds of genes, many of which encode antiviral effectors (36) (42,43). We also demonstrated recently that GILT suppresses the entry of SARS-CoV, but not other human CoVs (38). As reported herein, in our efforts to identify host on October 30, 2020 by guest http://jvi.asm.org/ Downloaded from factor(s) determining the differential susceptibility of two closely related human hepatoma cell lines to HCoV-OC43 infection, we found that LY6E potently suppresses the infectious entry of all the human CoVs, including the currently pandemic SARS-COV-2.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This system has been widely used in studies of coronavirus entry. To improve the expression level of S protein and the yield of pseudotyped virus, a codon-optimized S gene based on the sequence of isolate Wuhan-Hu-1 (2) was synthesized and used for production of pseudotyped virus as previously described for other human coronaviruses (HCoVs), including SARS-CoV, MERS-CoV, NL63, 229E, and OC43 (31,32). The pseudotyped virus was then used to infect 293T cells transfected with either empty vector, or a plasmid expressing APN (receptor for HCoV-229E), DDP4 (receptor for MERS-CoV), ACE1 or hACE2.…”
Section: Human Ace2 Serves As a Functional Receptor For Sars-cov-2mentioning
confidence: 99%